Characteristics Physicochemical and Determination Formaldehyde of Yellow Tofu at Kediri Regency - Jariyah; Andre Yusuf Trisna Putra; Rosita Dwi Agustin (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Yellow tofu is a typical Kediri food that is easily damaged because it contains protein and high water content. Tofu is prone to added harmful preservatives such as formaldehyde. Therefore, the purpose of this study was to determine the physicochemical properties and detection of formaldehyde in yellow tofu sold by producers in Kediri. seven samples were obtained from tofu producers in Kediri. The analyzes carried out were moisture content, ash, protein, hardness, curcumin detection, formalin detection and sensory evaluation. The data of the physico-chemical properties of yellow tofu was analyzed by ANOVA. Result of this study, showed that the chemical and physical composition varied between samples. Moisture of yellow tofu is between 65.13%-73.40%. Ash of yellow tofu is between 0.82-1.19%. Protein of yellow tofu is between 13.66-18.41%. The firmness of yellow tofu is between 12.30N-25.15N. The highest firmness was sample D. In this study, there is a positive correlation between firmness and texture sensory tests. Sensory test showed that bright yellow tofu received a positive score by the panelists. There is a positive correlation between detection of curcumin and color sensory test. The results showed that all samples were negative formalin.